Livability evaluation of urban environment based on Google Earth Engine and multi-source data: A case study of Kunming, China - Zhengyu Li; Zhifang Zhao; Tao Zhang (Ecological Indicators)
To quickly, accurately, and objectively assess urban environment livability, this study developed a comprehensive evaluation index—the Urban Environmental Livability Index (UELI)—using multi-source data from Google Earth Engine (GEE). The evaluation focused on three key dimensions: ecological environmental quality, the urban heat island effect, and socio-economic benefits. The main findings of the analysis were as follows: (1) From 2019 to 2023, Kunming’s livability was significantly affected by land use changes. (2) A total of 90.82% of Points of Interest (POI) facilities were located in livable areas, providing preliminary validation of the objectivity and rationality of the UELI. (3) The proportion of livable areas in Kunming in 2019, 2021, and 2023 was 48.36%, 41.67%, and 45.25%, respectively, indicating an initial decline followed by subsequent improvement. In conclusion, the study found that Kunming generally has sufficient livable space, with undeveloped livable areas primarily concentrated in the western part of Dongchuan, central Xundian, and eastern Shilin. The study also offers recommendations for regions where livability has undergone significant changes.